The effect of grit on the work engagement of the millennial generation - Rusdi, Muhammad; Purwaningrum, Evi Kurniasari; Ramadhan, Yoga Achmad (Jurnal Ilmiah Psikologi Terapan, 2023)
Employees of millennial generation are concerned about the sector since they are perceived to have less work engagement. This study used the positive psychology concept to empirically test the effect of grit on work engagement of 159 (N=159) millennial employees aged 20 to 40, with a minimum service period of one year. The method of this study was quantitative, and data collection used a questionnaire, namely the short version of the Utrecht Work Engagement Scale (UWES) and the Short Grit Scale (Grit-S), with 9 and 8 items for work engagement and grit, respectively. The sample used the purposive sampling technique, and the data were analyzed through a simple linear regression technique with the SPSS version 25.0 for windows. The analysis showed that grit positively affected work engagement with a value F(1.157) = 12.019, p = 0.001, R2 =0 .071, Radjusted = 0.065, and regression coefficient (β=0.603). The grit effect on work engagement was shown by the R square value of 0.071, meaning the grit variable of 7.1% influences the work engagement variation.